2013
DOI: 10.1002/oby.20100
|View full text |Cite
|
Sign up to set email alerts
|

A risk adjusted cost‐effectiveness analysis of alternative models of nurse involvement in obesity management in primary care

Abstract: Objective: Controlled evaluations are subject to uncertainty regarding their replication in the real world, particularly around systems of service provision. Using routinely collected data, we undertook a risk adjusted cost-effectiveness (RAC-E) analysis of alternative applied models of primary health care for the management of obese adult patients. Models were based on the reported level of involvement of practice nurses (registered or enrolled nurses working in general practice) in the provision of clinicalb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Training may range from two days (the TrueBlue study) to a university awarded postgraduate qualification with additional work experience (mental health nurse credential required to receive the MHNIP). Other RAC-E studies have shown that greater practice nurse involvement in the care of patients with diabetes and obesity is cost-effective [19,20]. Thus, in primary care settings where no specific framework for mental health training and support has been provided, practice nurse time might be better targeted towards diabetic or obese patient groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Training may range from two days (the TrueBlue study) to a university awarded postgraduate qualification with additional work experience (mental health nurse credential required to receive the MHNIP). Other RAC-E studies have shown that greater practice nurse involvement in the care of patients with diabetes and obesity is cost-effective [19,20]. Thus, in primary care settings where no specific framework for mental health training and support has been provided, practice nurse time might be better targeted towards diabetic or obese patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…The Primary Care Services Improvement Project (PCSIP) was a retrospective observational study, which used RAC-E methods to assign general practices to models of care based on observed differences in practice nurse activity in the provision of clinical-based services. Three case studies were conducted [19,20], with this paper reporting on the depression case study.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the focus of this research is the relationship between these variables among women and children who participate in the Wisconsin WIC program in order to provide evidence for future targeted interventions for at risk women and children to reduce risk of unhealthy weight and its sequalae. This study will help perinatal healthcare providers who have an opportunity to influence weight-related behaviors, including nutrition for the maternal-child dyad (Karnon et al 2013;Streuling et al 2010). As we better understand these modifiable factors and their contribution to weight-related risk to offspring, we can better plan interventions that can be delivered during pregnancy with the potential to influence multiple generations in a vulnerable population.…”
Section: Statement Of the Problem And Literature Reviewmentioning
confidence: 99%
“…For the patient, general practice provides a reputable, convenient, familiar and accessible setting with the opportunity for longterm follow up and support. There is evidence that nurse-led programs are effective in providing risk assessment, patient education, counselling and obesity management in primary care (Counterweight Project Team 2008, 2012Wood et al 2008;Sargent et al 2012;Karnon et al 2013) and that patients report high levels of satisfaction with nurses providing chronic disease management (Halcomb et al 2015). However, international evidence suggests that the perceived self-efficacy and legitimacy of GPs and practice nurses in providing weight management care is impeded by a lack of obesity-specific training (Nolan et al 2012;Henderson 2015).…”
Section: Introductionmentioning
confidence: 99%